2014
DOI: 10.1016/j.jalz.2014.04.387
|View full text |Cite
|
Sign up to set email alerts
|

O4‐01‐04: Amyloid in Dementia Associated With Familial Ftld: Not an Innocent Bystander

Abstract: Patients with frontotemporal lobar degeneration (FTLD) can show superimposed amyloid pathology, though the impact of amyloid on the clinical presentation of FTLD is not well characterized. This cross-sectional case-control study compared clinical features, fluorodeoxyglucose-positron emission tomography metabolism and gray matter volume loss in 30 patients with familial FTLD in whom amyloid status was confirmed with autopsy or Pittsburgh compound B-PET. Compared to the amyloid-negative patients, the amyloid-po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…44 Finally, our autopsy results showed that more than one-half of Aβ + nfvPPA/svPPA patients exhibit concomitant FTLD pathology, compared to only 6% of Aβ + lvPPA patients (see Fig 3), which is consistent with several case reports showing that positive Aβ biomarkers do not necessarily indicate that the clinical syndrome is primarily driven by AD pathology. [53][54][55] Previous reports have shown that ApoE4 allele was a risk factor for amyloid positivity but not for neuropathological diagnosis of AD in PPA patients. 12,23,25 This has potential clinical ramifications, as the increased a priori likelihood of detecting (comorbid) Aβ pathology in older patients and/or ApoE ε4 carriers should be considered when interpreting Aβ biomarkers in patients with PPA.…”
Section: Discussionmentioning
confidence: 99%
“…44 Finally, our autopsy results showed that more than one-half of Aβ + nfvPPA/svPPA patients exhibit concomitant FTLD pathology, compared to only 6% of Aβ + lvPPA patients (see Fig 3), which is consistent with several case reports showing that positive Aβ biomarkers do not necessarily indicate that the clinical syndrome is primarily driven by AD pathology. [53][54][55] Previous reports have shown that ApoE4 allele was a risk factor for amyloid positivity but not for neuropathological diagnosis of AD in PPA patients. 12,23,25 This has potential clinical ramifications, as the increased a priori likelihood of detecting (comorbid) Aβ pathology in older patients and/or ApoE ε4 carriers should be considered when interpreting Aβ biomarkers in patients with PPA.…”
Section: Discussionmentioning
confidence: 99%
“…The Similarly, previous reports have demonstrated that patterns of atrophy in autosomal dominant forms are different than in sporadic FTD, with more widespread cortical involvement, including the parietal lobes. All of the bvFTD cases had genetic testing performed through research using previously described methods (Naasan et al, 2016).…”
Section: Change Maps In Amyloid-negative and Nongene Carrier Bvftd mentioning
confidence: 99%